A Comparative Evaluation of Carcass Quality, Nutritional Value, and Consumer Preference of Oreochromis niloticus from Two Impoundments with Different Pollution Levels in Zimbabwe - Vimbai R. Hamandishe; Petronella T. Saidi; Venancio E. Imbayarwo-Chikosi; Tamuka Nhiwatiwa (International Journal of Food Science)
The objective of the study was to determine the quality and consumer preferences of Nile tilapia (Oreochromis niloticus) from two water bodies with different pollution levels and trophic states. Water quality assessment of the two impoundments was carried out. Fish were sampled from hypereutrophic Lake Chivero and oligomesotrophic Lake Kariba for proximate analysis, carcass quality, and sensory evaluation. Conductivity, dissolved oxygen, transparency, ammonia, total phosphates, reactive phosphates, and chlorophyll a were significantly different (P<0.05). Fish from Lake Kariba had significantly higher condition factors and lower fillet yields, while fish of length 10-20 cm, from Lake Chivero had significantly more fat. Lake Chivero fish were darker, greener, and less red while Lake Kariba fish were lighter, less green, and less red. Raw fish from Lake Kariba were significantly firmer, were less green and redder, had a stronger typical fish odour, and were more acceptable than Lake Chivero fish. Lake Chivero fish had a stronger foreign fish odour than their counterparts. No statistical differences were observed on fillet cooking losses, cooked fish sensory parameters, and acceptability. The fish could, however, not be safe due to possibility of toxins in water and feed (algae) which may bioaccumulate and ultimately affect other attributes of fish quality.